2015
DOI: 10.4236/ojf.2015.56055
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Disturbances and the Natural Vegetation Regeneration: A Case Study of a Forest Fragment Located in a Cuesta Relief Area, State of São Paulo, Brazil

Abstract: The present study has been conducted in one of the five natural vegetation fragments at the Experimental Farm Edgardia, in Botucatu, São Paulo State, Brazil. In the past the forest fragment suffered disturbances due to the selective exploitation of tree species and the use of part of the surface as pasture. The objectives of this research were to evaluate the structure and the dynamics of natural vegetation. Three phytosociological surveys (2006, 2010 and 2014) were carried out in a sampled area of one hectare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
1
6
0
5
Order By: Relevance
“…With a large number of S. fungiforme individuals sampled and a considerable effort in identifying host plants, we present robust data that indicates a preferential hostthe tree species C. floribundus -and four liana species that can be considered complementary hosts, since, together, these lianas corresponded to only 32 % of parasitized individuals. Supposing no preference at species level, we would expect a much higher host plant diversity among the hosts, considering that in these forests more than 60 tree species have been recorded (Fonseca & Rodrigues 2000;Jorge & Pereira 2015), along with a probably similar number of liana species, which are normally abundant in seasonal tropical forest fragments (Udulutsch et al 2004). Our observations complement the study conducted by Cardoso (2014), which suggested that S. fungiforme does not present a specific host.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…With a large number of S. fungiforme individuals sampled and a considerable effort in identifying host plants, we present robust data that indicates a preferential hostthe tree species C. floribundus -and four liana species that can be considered complementary hosts, since, together, these lianas corresponded to only 32 % of parasitized individuals. Supposing no preference at species level, we would expect a much higher host plant diversity among the hosts, considering that in these forests more than 60 tree species have been recorded (Fonseca & Rodrigues 2000;Jorge & Pereira 2015), along with a probably similar number of liana species, which are normally abundant in seasonal tropical forest fragments (Udulutsch et al 2004). Our observations complement the study conducted by Cardoso (2014), which suggested that S. fungiforme does not present a specific host.…”
Section: Discussionsupporting
confidence: 82%
“…The vegetation of these fragments is classified as seasonal tropical forest, a forest type in which 50-70 % of canopy species shed their leaves during the dry season. Previous studies on these forest fragments have recorded high tree species richness, with 61 species being reported by Fonseca & Rodrigues (2000) and 75 species by Jorge & Pereira (2015). The climate in this region is Cfa (Köppen classification, Alvares et al 2013), characterized by a rainy and warm season from September to April and a dry and cool season from May to August (rainfall below 50 mm), average annual rainfall being about of 1302 mm (Sentelhas et al 2003).…”
Section: Study Sitesmentioning
confidence: 83%
See 3 more Smart Citations